Keretapi Tanah Melayu (KTMB) services: the role of service quality and recovery towards satisfaction and loyalty / Nor Asiah Omar ... [et al.] - Omar, Nor Asiah; Abdul Ghani, Rohayu; Mohd Ramly, Suhaily; Hazirah Mohd Anim, Nur Aqilah; Nazri, Muhamad Azrin (Faculty of Business and Management, 2022)
TMB has been operating in Malaysia for decades, but the public transportation environment is changing, putting pressure on the industry to improve its services and facilities in order to satisfy customers. As a service-oriented corporation, it is critical for KTMB to preserve its reputation as the preferred high-speed rail service provider. Accordingly, this study intends to examine the impact of variables pertaining to service quality associated with KTMB service on customer satisfaction. Furthermore, this study examines the relationship between customer satisfaction and customer loyalty. Using the survey method, this study collected data from 406 KTM users, and subsequently, the data was analysed using SPSS. The finding of the analysis reveals that service recovery is the most influential factor towards customer satisfaction. Also, customer satisfaction significantly influences customer loyalty. In conclusion, the findings of this research assist the management of KTMB in enhancing customer satisfaction and loyalty.